The structure of the gas bladder of the spotted gar, Lepisosteus oculatus. (18th August 2014) - Icardo, José M.; Colvee, Elvira; Lauriano, Eugenia R.; Capillo, Gioele; Guerrera, Maria C.; Zaccone, Giacomo
ABSTRACT We report here on the macroscopic, light microscopic, and electron microscopic structure of the gas bladder (GB) of the spotted gar, Lepisosteus oculatus. The GB opens into the pharynx, dorsal to the opening of the oesophagus, through a longitudinal slit bordered by two glottal ridges. Caudal to the ridges, the GB is an elongated sac divided into a central duct and right and left lobes. The lobes are formed by a cranio‐caudal sequence of large air spaces that open into the central duct. The structure of the GB is that of a membranous sac supported by a system of septa arising from the walls of a central duct. The septa contain variable amounts of striated and smooth muscle might function to maintain the bladder shape and in providing contractile capabilities. The presence of muscle cells, nerves, and neuroepithelial cells in the wall of the GB strongly suggests that GB function is tightly regulated. The central duct and the apical surface of the thickest septa are covered by mucociliated epithelium. Most of the rest of the inner bladder surface is covered by a respiratory epithelium which contains goblet cells and a single type of pneumocyte. These two cell types produce surfactant. The respiratory barrier contains thick areas with fibrillar material and cell prolongations, and thin areas that only contain basement membrane material between the capillary wall and the respiratory epithelium. Lungs and GBs share many anatomical and histological features. There appears to be no clear criterion for structural distinction between these two types of respiratory organs. J. Morphol. 276:90–101, 2015. © 2014 Wiley Periodicals, Inc.